Does bureaucratic performance vary across authoritarian regimes?. Issue 1 (2nd January 2023) - Knox, Colin; Janenova, Saltanat
ABSTRACT: This article considers the performance of bureaucracies in two authoritarian states located in Central Asia, Kazakhstan and Kyrgyzstan. The former has been a consolidated authoritarian regime since its independence from the Soviet Union in 1991. The latter has oscillated between a form of parliamentary democracy and authoritarianism. We examine how the countries' bureaucracies perform under different systems of governance and find that Kazakhstan is more effective given its relatively stable political context, higher level of professionalism, and greater policy capacity amongst its officials, notwithstanding its consistent authoritarian leadership. When politicians interfere in the work of officials, it results in lower impartiality and constitutional uncertainty. This finding reaffirms previous research (using Quality of Government survey data) which calls for the separation of political and bureaucratic roles as a way of improving government effectiveness and reducing corruption.